2016
DOI: 10.3390/molecules21040453
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Hypoglycemic Effects of Poncirus trifoliata L. Extracts in High-Fat Diet C57BL/6 Mice

Abstract: The present study investigated the possible anti-obesity and hypoglycemic effects of Poncirus trifoliata L. extracts. Mature fruit were divided into flavedo (PF) and juice sacs (PJ), and extracts from them were tested on C57BL/6 mice fed a high-fat diet (HFD) for thirteen weeks. Both fruit extracts (40 mg/kg body weight, respectively) showed anti-obesity and hypoglycemic effects. Consumption of PF and PJ extracts reduced body weight by 9.21% and 20.27%, respectively. Liver and adipose weights, fasting glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…We found CIEE significantly reduced serum leptin levels and increased adiponectin levels in HFD-induced obese mice. Similarly, a previous study reported Poncritus trifoliate leaf extracts had an anti-obesity effect in HFD-fed mice (32). PPARα/γ is ligand-activated transcription factor, which plays role in glucose and protein metabolism and regulates preadipocytes proliferation and differentiation (33).…”
Section: Ciee (Mg/kg) -----------------------------------------------mentioning
confidence: 89%
“…We found CIEE significantly reduced serum leptin levels and increased adiponectin levels in HFD-induced obese mice. Similarly, a previous study reported Poncritus trifoliate leaf extracts had an anti-obesity effect in HFD-fed mice (32). PPARα/γ is ligand-activated transcription factor, which plays role in glucose and protein metabolism and regulates preadipocytes proliferation and differentiation (33).…”
Section: Ciee (Mg/kg) -----------------------------------------------mentioning
confidence: 89%
“…Another interesting example would be its anti‐obesity effect in high‐fat diet (HFD)‐induced obese mice models (Jia et al, ; Lu et al, ). Specifically, the extract of MF (40 mg/kg body weight) significantly reduced the body weight of HFD mice (Jia et al, ). Indeed, adipose weights, fasting glucose levels, and serum triglyceride levels in HFD mice were all significantly decreased by the treatment of MF (Jia et al, ).…”
Section: Miscellaneous Effectsmentioning
confidence: 99%
“…Specifically, the extract of MF (40 mg/kg body weight) significantly reduced the body weight of HFD mice (Jia et al, ). Indeed, adipose weights, fasting glucose levels, and serum triglyceride levels in HFD mice were all significantly decreased by the treatment of MF (Jia et al, ). Further molecular investigation determined that MF lowered the transcript levels of fatty acid synthase and stearoyl‐CoA desaturase 1 whereas increased those of carnitine palmitoyltransferase 1α and insulin receptor substrate 2 in the liver of HFD mice (Jia et al, ).…”
Section: Miscellaneous Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products isolated from fruit extracts have been associated with many positive health benefits, 1 such as being anticancer, 2 – 4 antioxidant, 5 , 6 anti-inflammatory, 7 and antiobesity. 8 More recently, much attention has been paid to flavonoids, a group of phenolic compounds, which have been shown to reduce the risk of major chronic diseases, such as obesity and diabetes. 9 Phloretin (2′,4′,6′-trihydroxy-3-(4-hydroxyphenyl)-propiophenone, Ph, Figure 1 ), a dihydrochalcone, which is the main component of the chalcone class of flavonoids, exists in apples, 10 pears, and strawberries.…”
Section: Introductionmentioning
confidence: 99%